2016
DOI: 10.1310/hpj5110-830
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the FDA Warning for Azithromycin and Risk for QT Prolongation on Utilization at an Academic Medical Center

Abstract: A US Food and Drug Administration (FDA) drug safety communication was released in March 2013, warning prescribers of the risk of QT prolongation associated with azithromycin. Overall azithromycin utilization and adherence to an inpatient QTc monitoring guideline during 8-month time periods before and after the warning were assessed to evaluate the impact of this warning on inpatient azithromycin utilization and QTc monitoring. Fifty-five patients were included in the prewarning time period and 50 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…All of the 70 publications included are observational studies based on routinely collected health data, which included health insurance or hospital records. Thus, no RCTs were found for the defined search period.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All of the 70 publications included are observational studies based on routinely collected health data, which included health insurance or hospital records. Thus, no RCTs were found for the defined search period.…”
Section: Resultsmentioning
confidence: 99%
“…In 66 out of 72 studies, intended changes in drug therapy were investigated with different results regarding their effectiveness. Contents of the safety warnings were described as effective in 28 out of 72 studies . In 12 studies, the authors concluded that the content of the safety warnings investigated did not lead to a change in drug therapy .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FDA issued a warning on May 17, 2012 on the risk of potentially fatal heart rhythm abnormalities associated with the drug. Employing a large claims database of over 12 million patients with greater than 23 million azithromycin prescriptions, Patel and colleagues [33] identified nearly 25% of patients were receiving another drug with QTc producing effects. The presence of pre-existing cardiac conditions was ~ 8.0%.…”
Section: More On the Importance Of Qtc Interval Prolongation And Patimentioning
confidence: 99%